2019
DOI: 10.1101/743914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-talks of glycosylphosphatidylinositol biosynthesis with glycosphingolipid biosynthesis and ER-associated degradation

Abstract: 16 17 18 Glycosylphosphatidylinositol (GPI)-anchored proteins and glycosphingolipids interact with 19 each other in the mammalian plasma membranes, forming dynamic microdomains. How their 20interaction starts in the cells has been unclear. Here, based on a genome-wide CRISPR-Cas9 21 genetic screen for genes required for GPI side-chain modification by galactose in the Golgi 22 apparatus, we report that b1,3-galactosyltransferase 4 (B3GALT4), also called GM1 23 ganglioside synthase, additionally functions in tra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 109 publications
1
10
0
Order By: Relevance
“…Recently, the Gal transferase was identified to be B3GALT4 [88], the Golgi-resident Gal transferase previously known to synthesize GM1 from GM2 [89,90]. B3GALT4 also synthesizes GA1 and GD1 from GA2 and GD2, respectively [89].…”
Section: Side Chain Modificationmentioning
confidence: 99%
“…Recently, the Gal transferase was identified to be B3GALT4 [88], the Golgi-resident Gal transferase previously known to synthesize GM1 from GM2 [89,90]. B3GALT4 also synthesizes GA1 and GD1 from GA2 and GD2, respectively [89].…”
Section: Side Chain Modificationmentioning
confidence: 99%
“…The mammalian B3GALT4 enzyme determines the synthesis of glycosphingolipids of the ganglioseries, e.g., GD1b, GM1 and GA1 ( Figure 1) and therefore is also known as the GM1-synthase (Amado et al 1998;Daniotti et al 1999;Miyazaki et al 1997). Interestingly, it was suggested that it could affect lipid concentrations by modifying lipoprotein receptors (Willer et al 2008) and more recently it was shown to catalyze the transfer of a Gal residue from UDP-Gal to the β1,4GalNAc side chain of glycosylphosphatdylinositol (GPI)-anchored proteins (Wang et al 2020). Our data indicate that the B3GALT4 functions are restricted to a few vertebrate species (Supplemental Figure 5B).…”
Section: Functional Divergence Of Gt31 Families In Vertebratesmentioning
confidence: 99%
“…This implies that enzyme activities for GPIanchor galactosylation and sialylation are diverse in brain tissues of different organisms. We recently reported that the percentages of Gal-modified and Sia-Gal-modified GPIglycans in CD59, a GPI-AP, were only 10% and 1% respectively, in HEK293 cells (14). Overexpression of B3GALT4 in HEK293 cells increased these percentages, indicating that B3GALT4-mediated Gal transfer was ratelimiting.…”
Section: Discussionmentioning
confidence: 98%
“…We recently identified PGAP4 (also known as TMEM246 or C9orf125) as a GPIspecific GalNAc transferase (12). More recently, we reported that B3GALT4, which is also known as ganglioside GM1 synthase, also acts as a Gal transferase for the GPI-GalNAc sidechain (14). Although these achievements have progressed our understanding of GPI-GalNAc side-chain, the biosynthesis pathway of the GPIglycan structure is still incomplete.…”
Section: Introductionmentioning
confidence: 99%